Excel 2010 formulas - Walkenbach, John (Mr. Spreadsheet?s bookshelf, 2010)
A reference collection of formulas for spreadsheet challenges covers operators, nesting, functions, error values, naming, cell formatting, protection options, array formulas, pivot tables, and auditing